2004
DOI: 10.1016/j.cell.2004.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Cln3 Activates G1-Specific Transcription via Phosphorylation of the SBF Bound Repressor Whi5

Abstract: G1-specific transcriptional activation by Cln3/CDK initiates the budding yeast cell cycle. To identify targets of Cln3/CDK, we analyzed the SBF and MBF transcription factor complexes by multidimensional protein interaction technology (MudPIT). Whi5 was identified as a stably bound component of SBF but not MBF. Inactivation of Whi5 leads to premature expression of G1-specific genes and budding, whereas overexpression retards those processes. Whi5 inactivation bypasses the requirement for Cln3 both for transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
561
4
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(598 citation statements)
references
References 54 publications
32
561
4
1
Order By: Relevance
“…Early studies showed that cells lacking Swi6 produced an intermediate constitutive level of transcripts for other Swi6 target genes (Dirick et al 1992;Lowndes et al 1992), suggesting that Swi6 performs a regulatory function that is both positive and negative within the cell cycle. This hypothesis is supported by the recent discovery of Whi5, which associates with Swi4/Swi6 complexes during early G 1 and dissociates when the complex is activated ( Jorgensen et al 2002;Costanzo et al 2004;de Bruin et al 2004). Activation of Swi4/Swi6 complexes requires the Cln3 cyclin and the Cdc28 cyclindependent kinase, which phosphorylates Whi5 and promotes its dissociation.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Early studies showed that cells lacking Swi6 produced an intermediate constitutive level of transcripts for other Swi6 target genes (Dirick et al 1992;Lowndes et al 1992), suggesting that Swi6 performs a regulatory function that is both positive and negative within the cell cycle. This hypothesis is supported by the recent discovery of Whi5, which associates with Swi4/Swi6 complexes during early G 1 and dissociates when the complex is activated ( Jorgensen et al 2002;Costanzo et al 2004;de Bruin et al 2004). Activation of Swi4/Swi6 complexes requires the Cln3 cyclin and the Cdc28 cyclindependent kinase, which phosphorylates Whi5 and promotes its dissociation.…”
supporting
confidence: 53%
“…Once bound to SCB elements, Swi4/Swi6/ Whi5 recruits mediator, but this takes place well before the complex is activated by Cln3/Cdk. Whi5 dissociates and transcription ensues (Costanzo et al 2004;de Bruin et al 2004), with the further recruitment of PolII, TFIIB, and TFIIH (Cosma et al 2001).…”
mentioning
confidence: 99%
“…As protein synthesis seems to increase exponentially during the cell (a) scheme of the start network with components and interactions. Briefly, the Cdk-cyclin complex formed by Cln3 [16][17][18][19][20] and Cdc28 21 phosphorylates the transcriptional repressor Whi5 22,23 and activates sBF (swi6/swi4) and mBF (swi6/mbp1) transcription factors 14 to induce the G1/s regulon 15 and trigger cell cycle entry. Whi3 and Ydj1 act as negative and positive regulators, respectively, of release of cyclin Cln3 from the ER [31][32][33] to allow its accumulation in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Whi5 22,23 binds G1/S transcription factors 14 to inhibit their activity in the nucleus during G1. Thus, we analysed cells deficient for Whi3 (Fig.…”
Section: Cell Size At Start Is Dictated By Volume Growth Rate In G1mentioning
confidence: 99%
“…In the case of SBF, this is probably due to Whi5-mediated inactivation (Costanzo et al 2004;De Bruin et al 2004), which involves recruitment of the Rpd3L histone deacetylase (Takahata et al 2009). SBF is subsequently activated through phosphorylation of Whi5 by the Cln3-Cdc28 kinase (Costanzo et al 2004;De Bruin et al 2004).…”
Section: Mechanism Of Histone Gene Regulation During the Cell Cyclementioning
confidence: 99%